Condensed Capitalism: Campbell Soup and the Pursuit of Cheap Production in the Twentieth Century - Penfold, Steve (Labour / Le Travail, 2010)
The article reviews the book, "Condensed Capitalism: Campbell Soup and the Pursuit of Cheap Production in the Twentieth Century," by Daniel Sidorick.
Keywords: BOOKS -- Reviews; CAMPBELL Soup Co. -- History; CONDENSED Capitalism: Campbell Soup & the Pursuit of Cheap Production in the 20th Century (Book); Nonfiction; SIDORICK, Daniel